Remarks on Schrödinger operators with singular matrix potentials - Molyboga, V. M.; Mikhailets, V. A. (Methods of Functional Analysis and Topology, 2013)
In this paper, an asymmetric generalization of the Glazman-Povzner-Wienholtz theorem is proved for one-dimensional Schrödinger operators with strongly singular matrix potentials from the space H_loc^-1(R, C^m× m). This result is new in the scalar case as well.